The Spectrum of Childhood-Onset Lower Motor Neuron Disease of Spinal Muscular Atrophy Phenotype Associated with Survival Motor Neuron-2 Gene Deletion - Ganguly, Somenath; Chakraborty, Durga Prasad; Roychoudhury, Satyabrata; Nandi, Madhumita; Das, Suman (Journal of Pediatric Neurology, 2024)
Pediatric lower motor neuron disease is clinically and genetically heterogeneous. We characterized disease progression among children with the spinal muscular atrophy (SMA) phenotype having 2:0 (group A) and 2:1 (group B) of the survival motor neuron 1/2 (SMN1:SMN2) genotype over 1 year. We included children aged 0 to 12 with the SMA phenotype between January 2018 and December 2021. Their demographic, clinical (Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders [CHOP-INTEND] scores), electrophysiological, radiological, and genetic data were collected from past medical records. The sequential CHOP-INTEND scores and the compound muscle action potential (CMAP) amplitudes were compared using an analysis of covariance test, controlling for age and sex. A linear regression was run to determine the association between the ages of the patients and the CHOP-INTEND scores. Among nine children in group A and six in group B, the decline of the mean (standard deviation) CHOP-INTEND score from the initial value to the 12th-month follow-up value was significant only in group A. CHOP-INTEND scores did not significantly differ between the two groups at the first admission but were significantly lower in group A at the subsequent visits. Group A patients had significantly lower CMAP amplitudes than patients in group B. There was a moderate, negative association between the age of patients and the CHOP-INTEND scores in group A. Group A patients had a significantly higher age-dependent decline in CHOP-INTEND scores and CMAP values than group B, although their age and the severity of weakness did not significantly differ at presentation.
Keywords: lower motor neuron diseases; SMN2; MLPA; CHOP-INTEND score; CMAP amplitudes